ANIMAL RANGER WEBSITE DESIGN: ANIMAL ADOPTION PLATFORM - Ferdianto, Ferdianto; Witarsyah, Witarsyah; Theodore, William; Avrialdo, Apollos; Naufal, Faiq (Bina Nusantara University, 2023)
Currently, both government and non-government organizations such as animal shelters performing rescue and adoption of stray animals. Although the ecosystem is not running well, some animal lovers still adopt stray animals from the shelter. Information that is limited and unclear is also faced by shelters and animal lovers in performing rescue and adoption. We created the Animal Ranger website based on problems. Analysis and system planning are based on interviews with animal shelters and questionnaires for animal lovers, using the UML method. Animal Ranger website was expected to encourage stray animal rescue and adoption of the ecosystem by animal lovers and animal shelters